Comparison of the welding deformation of mismatch and normal butt joints produced by laser-arc hybrid welding. (August 2018) - Li, Liqun; Xia, Hongbo; Ma, Ninshu; Pan, Bo; Huang, Yichen; Chang, Shuai
Abstract: A reliable numerical model is developed to predict the deformation of mismatch and normal butt-welded joints after laser and gas metal arc hybrid welding (Laser-GMAW). A smaller deflection is produced in the mismatch joint as a result of a more uniform weld profile along the thickness direction, while a larger shrinkage deformation is obtained as a result of the higher heat input compared to the normal joint. The transverse plastic strain is much larger than the longitudinal plastic strain for both joints. An interruption is observed at the bottom surface of the mismatch joint owing to the discontinuity of the weld profile. The calculated inherent deformation, based on the plastic strain, is much larger along the transverse direction than along the longitudinal direction and it is also the dominating welding deformation. The deformation of a pipe assembled with a longitudinal welding line is predicted from the calculated inherent deformation parameters. A smaller roundness (ΔR) and deflection (ΔZ) are produced in the mismatch joint due to its smaller inherent bending deformation compared to the normal joint.